DOI: 10.11606/d.18.2013.tde-29112013-084714
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição de ácido polifosfórico em ligantes asfálticos de diferentes fontes

Abstract: Aos meus pais, pelo amor incondicional, por todo o incentivo à minha formação e por acreditarem nos meus sonhos. Aos meus irmãos Ivo e Bruno por estarem sempre ao meu lado me fortalecendo, por todo carinho e amizade. Ao professor Adalberto Leandro Faxina, pela orientação, apoio, amizade, confiança e pelas incontáveis intervenções valiosas. À professora Sandra Soares, por toda a atenção, dedicação e orientação durante esse trabalho e na minha formação acadêmica. Ao professor Hussain U. Bahia pela atenção, por p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…However, Isacsson (2006, 2007) reported that the improvement in the mechanical properties of the asphalt concrete with the addition of the PPA depends on the composition of the base asphalt binder and the amount of PPA used to produce the modified binder. This was also observed by Pamplona (2013) after studying the incorporation of the PPA to binders obtained from different crude sources.…”
Section: Statementsupporting
confidence: 53%
See 1 more Smart Citation
“…However, Isacsson (2006, 2007) reported that the improvement in the mechanical properties of the asphalt concrete with the addition of the PPA depends on the composition of the base asphalt binder and the amount of PPA used to produce the modified binder. This was also observed by Pamplona (2013) after studying the incorporation of the PPA to binders obtained from different crude sources.…”
Section: Statementsupporting
confidence: 53%
“…The exponent B is related to the asphalt binder sensibility to the strain level. For higher values of the exponent B, the slope of the fatigue curve increases, indicating that the material is more sensitive to variations in the strain levels in the pavement (NUÑEZ, 2013;PAMPLONA, 2013). The exponent B corresponds to the double of the alpha values and because of that it expresses directly the damage evolution rate of the material.…”
Section: Parameters a And B Of The Fatigue Modelmentioning
confidence: 99%
“…This test assesses the asphalt fatigue resistance by cyclic loading using a linear increase of the amplitude load. The amplitude sweep is performed in the DSR at a 19 ºC intermediate temperature of the pavement, representing the fatigue damage rather than the parameter expressed by G*sen δ (Pamplona, 2013;Martins, 2014). The binder is tested after short-term aging.…”
Section: Linear Amplitude Sweep -Las [Dnit 439/2022; Dnit (2022)]mentioning
confidence: 99%
“…Hintz et al (2011) também concluíram que o enrijecimento provocado pelo envelhecimento tem um efeito positivo na resistência à fadiga para níveis de tensão mais baixos, mas tem um efeito negativo para níveis de tensão mais elevados. Pamplona (2013), utilizando o LAS modificado, também verificou que o envelhecimento a longo prazo contribui para o aumento da tolerância à fadiga de ligantes asfálticos modificados com PPA, na extensão em que o envelhecimento oxidativo atua no sentido de aumentar o comprimento da trinca na ruptura. Em relação à adição de PPA, Pamplona (2013) observou que a tolerância à fadiga dos ligantes asfálticos aumenta com a adição de PPA, embora o efeito do PPA tenha intensidades diferentes para diferentes tipos de ligante asfáltico.…”
Section: Introductionunclassified